Implementasi Putusan No. 27/PhPu.D-VIII/2010 Mengenai Perselisihan hasil Pemilihan umum Kepala Daerah Kabupaten Lamongan - Siahaan, Maruarar (Mahkamah Konstitusi Republik Indonesia, 2011)
The objection of petitioner on the recount results by the Election Commission of Lamongan on the orders of the interlocutory injunction of the Court ,was not examined further and be heard simultaneously with the Commission report on the implementation of interlocutory injunction in a hearing open to the public, and thereafter immediately the Constitutional Court considered the objection has no juridical value. The final decision then confirmed the Commission’s decision on the result of the recounting. Nonetheless, the function of the interlocutory verdict must be understood as a mechanism to prepare the final verdict. Therefore, the results of the interlocutory verdict must be heard and examined in a session open to the parties and the public, to be used as the basis for a final decision. The hearing process before the final verdict has been decide, does not end with the announcement of the interlocutory verdict. Implementation of the Constitutional Court decision on the district election dispute has been uninhibited, but in one case. Although the number is quantitatively insignificant, it is qualitatively very important as a lesson learned in that the Court is still in need to improve its performance in guarding the consolidation of democracy.